TBAI-catalyzed C–N bond formation through oxidative coupling of benzyl bromides with amines: a new avenue to the synthesis of amides - Kumar D.; Maury S.K.; Kumari S.; Kamal A.; Singh H.K.; Singh S.; Srivastava V. (My University, 2025)
A new green approach for the synthesis of amide through TBAI-catalyzed oxidative coupling of benzyl bromides with amine was developed in the presence of tert-butyl hydroperoxide (TBHP) as an oxidant. Various electron-donating and withdrawing groups containing benzyl bromides and various amines, were subjected to the reaction and transformed to the corresponding amide in good to excellent yields. © 2022 Taylor & Francis Group, LLC.